Inadequate community engagement hamstrings sustainable wildlife resource management in Zambia. (27th July 2019) - Milupi, Inonge D.; Somers, Michael J.; Ferguson, Willem
Abstract: We propose improvements for addressing the inadequate sustainable use of wildlife resources in the community‐based natural resource management (CBNRM) programme in game management areas (GMAs) using case study data from Mumbwa and Lupande GMAs in Zambia. Firstly, we assess the sustainability of wildlife resources in these GMAs using design principles for enduring common pool institutions. Secondly, we propose the steps required to address the lack of sustainability of wildlife resources in the CBNRM programme in the two GMAs by building on indicators suggested by Ostrom's principles. The resource use patterns in the two GMAs were assessed according to their socio‐economic and institutional factors. Comparisons were made between the two GMAs in relation to Ostrom's design principles. Accordingly, the combination of socio‐economic and institutional factors restrains the sustainable use of wildlife resources in the two GMAs. Unless the Zambian government provides local communities with meaningful decision‐making powers and benefits for the utilisation and management of wildlife, this resource is likely to disappear outside national parks. Résumé: Nous proposons des améliorations pour remédier à l'utilisation durable inadéquate des ressources fauniques dans le programme de gestion communautaire des ressources naturelles (CBNRM) dans les Aires de gestion de la faune (GMAs) à l'aide de données d'études provenant de GMAs de Mumbwa et de Lupande en Zambie. Premièrement, nous évaluons la durabilité des ressources fauniques dans ces GMAs en utilisant des principes de conception pour la durabilité des institutions du bien collectif. Deuxièmement, nous proposons les mesures nécessaires pour remédier au manque de durabilité des ressources fauniques au programme CBNRM dans les deux GMAs, en nous appuyant sur les indicateurs suggérés par les principes d'Ostrom. Les modèles d'utilisation des ressources dans les deux GMAs ont été évalués selon leurs facteurs socioéconomiques et institutionnels. Des comparaisons ont été faites entre les deux GMAs par rapport aux principes de conception d'Ostrom. En conséquence, la combinaison des facteurs socioéconomiques et institutionnels limite l'utilisation durable des ressources fauniques dans les deux GMAs. À moins que le gouvernement zambien ne donne aux communautés locales des pouvoirs de décisions et des avantages pour l'utilisation et la gestion de la faune, cette ressource est susceptible de disparaître en dehors des parcs nationaux.